Estimation of the surface sulfur content of cellulose nanocrystals prepared by sulfuric acid hydrolysis - Abitbol, Tiffany; Kloser, Elisabeth; Gray, Derek G. (Cellulose (London), 2013)
ABSTRACT The conditions required for the accurate measurement of the sulfur content of cellulose nanocrystals (CNCs) by conductometric titration are discussed. CNCs from sulfuric acid hydrolysis are electrostatically stabilized in aqueous suspension due to the introduction of charged sulfate ester groups onto the surface of the crystallites during reaction. The sulfur content thus largely reflects the surface charge of the crystals, and is crucial to the characterization and understanding of material properties. Conductometric titration is commonly used to quantify the sulfur content of CNCs, however, the exhaustive removal of free acid by dialysis and the necessity, type, quantity and duration of ion-exchange resin treatments are not always consistent. Here we explore the standard conditions of dialysis, ion-exchange, and the reproducibility of titration results. Extensive dialysis is found to be effective in the removal of free acid, but similar results are also achieved in shorter times and with less water using membrane ultrafiltration. It is also shown that the conditions of ion-exchange most commonly employed in the literature can lead to inaccurate sulfur contents. Finally, good agreement is obtained between the sulfur contents of different CNC batches prepared using the same hydrolysis conditions, and from titration and elemental analysis when thoroughly purified, well-dispersed samples, and appropriate resin conditions are used.